2015
DOI: 10.1080/19393555.2014.998847
|View full text |Cite
|
Sign up to set email alerts
|

Locking Out the Investigator: The Need to Circumvent Security in Embedded Systems

Abstract: Embedded devices are becoming ubiquitous in both domestic and commercial environments. Although smartphones, tablets, and video game consoles are all labeled by their primary function, most of these devices offer additional features and are capable of additional interactivity. Given the proprietary nature of such devices in terms of hardware and software and the protection mechanisms incorporated into these systems, it is and will continue to be extremely difficult to use “traditional digital forensics” method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Liles et al (2009) explored the legal issues facing forensics experts which highlighted legal concerns including the interpretation of legislation. Read et al (2015) focused on the legal and ethical issues of jailbreaking and hardware modification to access devices, and Stoykova et al (2022) highlighted the legal and technical issues relating to the reverse engineering of file systems. Exploiting vulnerabilities in some cases provides the investigator access to devices that would otherwise be inaccessible.…”
Section: Prior Workmentioning
confidence: 99%
“…Liles et al (2009) explored the legal issues facing forensics experts which highlighted legal concerns including the interpretation of legislation. Read et al (2015) focused on the legal and ethical issues of jailbreaking and hardware modification to access devices, and Stoykova et al (2022) highlighted the legal and technical issues relating to the reverse engineering of file systems. Exploiting vulnerabilities in some cases provides the investigator access to devices that would otherwise be inaccessible.…”
Section: Prior Workmentioning
confidence: 99%
“…Specific security countermeasures for RTES can be implemented in two stages: (i) identify specific attacks that could threaten the systems; and (ii) implement security-guaranteed services, overcoming the challenges of real-time performance and energy consumption [27]. The study in [88] showed how security measures could be circumvented in different platforms. This demonstrates the importance of highly robust solutions and their availability for a long period.…”
Section: B Security Countermeasures Of Essmentioning
confidence: 99%
“…A cyber-attack could produce severe consequences, e.g., the damage of all systems connected to the targeted system. Hence, it is important to consider the impacts and responses to potential cyber incidents, caused by attacks on these levels [95], [27], [130], [131], [126].…”
Section: ) Impact Of Cyber Attacksmentioning
confidence: 99%
“…Several hacks have been developed that circumvent the security measures on the 3DS and allow third-party (homebrew) applications to be installed. As discussed in [23], these mechanisms could be used as new vectors to extract data from embedded systems. In the case of the 3DS, a number of applications and game titles have been shown to be exploitable.…”
Section: Forensic Valuementioning
confidence: 99%